Analysis of an environmental crime committed by a legal entity at the Marituba landfill (RMB) and its socio-environmental impacts (Research, Society and Development, 2023)
The objective of this study is to analyze the practical environmental crimes by the companies Guamá Treatment of Residues Ltda and Revita Engenharia S.A, and the socio-environmental impacts provoked in the ecosystem. These companies were condemned by the Public Ministry of the State of Pará (MPPA), for non-compliance with environmental standards after the implementation of the Sanitary Landfill in the municipality of Marituba located in the Metropolitan Region of Belém (RMB). The methodological procedure used in this work was qualitative, analyzing bibliographic, journalistic, documentary material and technical reports. In general, the search for information on solid waste management in the RMB was carried out through the analysis of documents prepared by the MPPA and, finally, the socio-environmental impacts caused to the communities in the research area were identified. The results of this work pointed out important points about the characteristics of the sanitary landfill, in which the perception and conditions prevailed, in which companies were condemned for environmental crimes, where the social contradictions and territorial reorganizations that such interventions caused in urban centers in the RMB were noted.